Sistem Reservasi Perawatan Gigi Berbasis Website Pada Klinik Marvel Dental - Chavia Rossyerin Prabowo Sutjiadi; Agus Budi Dharmawan; Novario Jaya Perdana (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
In the midst of rapid global business development, information technology plays an important role in the health sector, especially in improving the quality of services to the community. The computerized system supports business success by speeding up and making various types of work more efficient, however Marvel Dental Clinic still has not implemented information technology to improve the quality of its services so there are several problems that arise, namely the reservation process is currently still done manually. Where this is a manual process, when patients make a reservation, they need to contact them via WhatsApp. The manual reservation process results in uncertainty in knowing the waiting time and uncertainty in getting an admin response. Another problem is that if you make a reservation for dental care using Whatsapp, if many patients make reservations, reservation applications can be piled up, so that the clinic does not know that there are reservations from these patients. This research aims to design and build a website-based dental care reservation system using the PHP programming language by utilizing the Laravel framework and the SDLC Prototype development method. This system makes it easier for patients to order services online and manage schedules more efficiently.